2000
DOI: 10.1128/jvi.74.19.8884-8892.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Bursal T Lymphocytes Induced by Infectious Bursal Disease Virus

Abstract: Infectious bursal disease virus (IBDV) is an avian lymphotropic virus that causes immunosuppression.When specific-pathogen-free chickens were exposed to a pathogenic strain of IBDV (IM), the virus rapidly destroyed B cells in the bursa of Fabricius. Extensive viral replication was accompanied by an infiltration of T cells in the bursa. We studied the characteristics of intrabursal T lymphocytes in IBDV-infected chickens and examined whether T cells were involved in virus clearance. Flow cytometric analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
78
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 42 publications
9
78
0
3
Order By: Relevance
“…In a 51Cr-release cytotoxicity assay, non-specific cytotoxic cell reactivity was detected both after in ovo and/or at hatch vaccinated chicks against In IBDV infected chickens during the peak infiltration of T-cells noted at 7 days post infection, CD8+ T-cells were relatively higher in number than CD4+ T-cells (49,99). T-cell aggregates may be important in bursal recovery and follicular repopulation after IBDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In a 51Cr-release cytotoxicity assay, non-specific cytotoxic cell reactivity was detected both after in ovo and/or at hatch vaccinated chicks against In IBDV infected chickens during the peak infiltration of T-cells noted at 7 days post infection, CD8+ T-cells were relatively higher in number than CD4+ T-cells (49,99). T-cell aggregates may be important in bursal recovery and follicular repopulation after IBDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the pathology caused by classical virulent and variant IBDV and of those relating to the immune clearance of the virus have begun to be elucidated. Tanimura & Sharma (1997) and Kim et al (2000) have suggested that T cells are induced during an IBDV infection in the bursa, but phenotypic characterization is still required. Rodenberg et al (1994) studied changes in the T-cell subsets within the blood, bursa, spleen and thymus after infection with classical virulent IBDV and suggested that, although the number of immunoglobulin (Ig)M ' cells in the bursa and spleen decreased significantly, the relative proportions of CD4 ' and CD8 ' T cells did not change.…”
Section: Introductionmentioning
confidence: 99%
“…One of the genes (TLR3) was also subjected to RT-PCR that confirmed the results of microarray. Microarray analysis and qRT-PCR were performed on day 3 post-infection to correspond with the known peak of IBDV acute phase [10,11]. The basal expression levels of IL15 and IL16 were different between mock-infected indigenous Vs commercial chickens with inherent increased IL-16 expression in indigenous chickens indicating inherent genetic differences between these two groups of chickens.…”
mentioning
confidence: 99%